Alternative Approaches to Adenotonsillectomy and Continuous Positive Airway Pressure (CPAP) for the Management of Pediatric Obstructive Sleep Apnea (OSA): A Review. (4th July 2020) - Rana, Mandeep; August, Joshua; Levi, Jessica; Parsi, Goli; Motro, Melih; DeBassio, William
Abstract : Continuous positive airway pressure (CPAP) is considered first-line treatment in the management of pediatric patients without a surgically correctible cause of obstruction who have confirmed moderate-to-severe obstructive sleep apnea (OSA). The evidence supports its reduction on patient morbidity and positive influence on neurobehavioral outcome. Unfortunately, in clinical practice, many patients either refuse CPAP or cannot tolerate it. An update on alternative approaches to CPAP for the management of OSA is discussed in this review, supported by the findings of systematic reviews and recent clinical studies. Alternative approaches to CPAP and adenotonsillectomy for the management of OSA include weight management, positional therapy, pharmacotherapy, high-flow nasal cannula, and the use of orthodontic procedures, such as rapid maxillary expansion and mandibular advancement devices. Surgical procedures for the management of OSA include tongue-base reduction surgery, uvulopalatopharyngoplasty, lingual tonsillectomy, supraglottoplasty, tracheostomy, and hypoglossal nerve stimulation. It is expected that this review will provide an update on the evidence available regarding alternative treatment approaches to CPAP for clinicians who manage patients with pediatric OSA in daily clinical practice.